Effects of Helicobacter pylori adhesin HopQ binding to CEACAM receptors in the human stomach - Nguyen, Quynh Anh; Schmitt, Leonard; Mejías-Luque, Raquel; Gerhard, Markus (Frontiers in Immunology, 2023)
Helicobacter pylori has developed several strategies using its diverse virulence factors to trigger and, at the same time, limit the host’s inflammatory responses in order to establish a chronic infection in the human stomach. One of the virulence factors that has recently received more attention is a member of the Helicobacter outer membrane protein family, the adhesin HopQ, which binds to the human Carcinoembryonic Antigen-related Cell Adhesion Molecules (CEACAMs) on the host cell surface. The HopQ-CEACAM interaction facilitates the translocation of the cytotoxin-associated gene A (CagA), an important effector protein of H. pylori, into host cells via the Type IV secretion system (T4SS), leading to aberrant host signaling cascades. In the last few years, many studies have emphasized the prerequisite role of the HopQ-CEACAM interaction not only for the adhesion of this pathogen to host cells but also for the regulation of cellular processes. This review summarizes recent findings about the structural characteristics of the HopQ-CEACAM complex and the consequences of this interaction in gastric epithelial cells as well as immune cells. Given that the upregulation of CEACAMs is associated with many H. pylori-induced gastric diseases including gastritis and gastric cancer, these data may enable us to better understand the mechanisms of H. pylori’s pathogenicity.